Impact of Antiarrhythmic Drugs on the Outcome of Short QT Syndrome - El-Battrawy, Ibrahim; Besler, Johanna; Li, Xin; Lan, Huan; Zhao, Zhihan; Liebe, Volker; Schimpf, Rainer; Lang, Siegfried; Wolpert, Christian; Zhou, Xiaobo; Akin, Ibrahim; Borggrefe, Martin (Frontiers in Pharmacology, 2019)
Short QT syndrome (SQTS) is associated with sudden cardiac arrest. There are limited data on the impact of antiarrhythmic drugs on the outcome of SQTS. Materials and Methods: We studied data that describe the clinical outcome of 62 SQTS patients treated with antiarrhythmic drugs, who were recruited from a pool of patients diagnosed in our institution and also from known databases after a systematic search of the published literature. Results: Sixty-two SQTS patients treated with antiarrhythmic drugs were followed up over a median timeframe of 5.6 years (interquartile range 1.6–7.7 years). Six patients, in particular, received multiple drugs as a combination. Of the 55 patients treated with hydroquinidine (HQ), long-term prophylaxis was documented in 41 patients. Fourteen patients stopped treatment due to the following reasons: gastrointestinal intolerance (n = 4), poor compliance (n = 8), and no QTc prolongation (n = 2). Of the 41 patients treated with HQ, the QTc interval increased from 313.5 ± 17.2 to 380.1 ± 21.2 ms. Thirteen of the 41 patients suffered from at least one or more ventricular tachyarrhythmias (VAs) before HQ initiation. VAs are reduced in incidence after HQ treatment (13/41: 31% versus 3/41: 7.3%, p < 0.001). Conclusion: HQ increases the corrected QT interval and prevents VAs in the majority of the patients in this cohort. HQ is safe for use in SQTS patients, particularly due to its low rate of side effects. Other antiarrhythmic drugs might be useful, but the data justifying their use are sparse.